Gritos do silêncio: o professor frente à violência sexual contra crianças e adolescentes no espaço escolar - Vagliati, Ana Carla (2014)
The study aimed to know how teachers deal with sexual violence in school environment: if they know to identify signs of sexual violence in their students and, what are their actions in front of this phenomena. For this, we performed an empirical-bibliographic research of qualitative and quantitative nature. We listed as categories of analysis the psychoanalysis and education, sexual violence, sexuality and sex education. We took these categories as historical product and dimension of social human praxis, circumscribing to the theoretical methodological referential from historical-dialetic materialism. For the bibliographic research, we did a search for scientific-academic productions, using describers like our categories of analysis, in database of CAPES, Scielo, BDTD and the Public Domain. We also did a data collection at state universities, located in the state of Parana, verifying the ones which had Stricto Sensu Post-Graduation. We located twelve (12) universities. We found seventeen (17) dissertations and thesis, which, however, didn t reflect the aim of this study; we also didn t find products that related the four (4) researched categories. The field research came from the collection of data from the Centro de Referência Especializado em Assistência Social (CREAS), which provided us the number of children and teenagers treated in the year 2013, victims of sexual violence and the schools where they studied. We conducted individual interviews with thirty-one (31) teachers in eleven (11) schools in the municipal and state network from the municipality of Francisco Beltrão - PR. Anchored in the bibliographic and field research we noted limitations of teachers in identifying signs of sexual violence in their students. Through undertaken data, we conclude that lacks investment in municipal public policy concerning the prevention and combating sexual violence against children and adolescents, as well as in teacher formation in sexuality and sex education to deal with this phenomenon. A percentage of 22% of teachers have been trained in the area of sexuality and sexual violence, one of which received training in higher education and the other through lectures and continuing education. We emphasize that the teaching time of teachers is between three (3) to thirty-six (36) years, and the majority has been acting for more than ten (10) years. So even considered important agents in combat, confrontation, identification and prevention of sexual violence, teachers realize that the requirement of working with sex education is beyond the knowledge that their training provides them. We advocate the formation of teachers in emancipatory sexuality education, with inclusion of studies on sexual violence as a tool of great importance to the prevention and identification of sexual violence in school environment. Such formation may encourage teachers to listen to the screams silenced by the dramatic sexual experiences that many of our children and teenagers are undergoing.